2012
DOI: 10.1007/s00415-012-6498-2
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of basilar artery occlusion in patients aged 75 years or older in the Basilar Artery International Cooperation Study

Abstract: Patients with an acute basilar artery occlusion (BAO) have a high risk of long-lasting disability and death. Only limited data are available on functional outcome in elderly patients with BAO. Using data from the Basilar Artery International Cooperation Study, we aimed to determine outcomes in patients ≥75 years. Primary outcome measure was poor functional outcome (modified Rankin scale score 4–6). Secondary outcomes were death, insufficient vessel recanalization (defined as thrombolysis in myocardial infarcti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 10 publications
(13 reference statements)
0
8
1
Order By: Relevance
“…The predictive value of the NIHSS score for the presence of artery occlusion was suggested to be poorer in the posterior circulation than in the anterior circulation , and the cut‐off value for baseline NIHSS for favourable outcome was found to be lower in posterior circulation than in anterior circulation strokes . Last but not least, in line with the BASICS registry showing no effect of age >75 years on the incidence of sICH age was not found to be an independent risk factor either .…”
Section: Discussionmentioning
confidence: 78%
“…The predictive value of the NIHSS score for the presence of artery occlusion was suggested to be poorer in the posterior circulation than in the anterior circulation , and the cut‐off value for baseline NIHSS for favourable outcome was found to be lower in posterior circulation than in anterior circulation strokes . Last but not least, in line with the BASICS registry showing no effect of age >75 years on the incidence of sICH age was not found to be an independent risk factor either .…”
Section: Discussionmentioning
confidence: 78%
“…Third, the time from onset to treatment, an important prognostic factor for the elderly patients in our study, tended to be shorter than that in patients ⩾75 years of age with symptom onset within 24 h in the BASICS registry. 22 We compared the number and proportion of patients during five time periods stratified by time to treatment between the elderly patients in the BASICS and BASILAR registries: <3 h: 50 (34.7%) versus 91 (50.0%); 4–6 h: 50 (34.7%) versus 59 (32.4%); 7–9 h: 17 (11.8%) versus 16 (8.8%); 10–12 h: 13 (9.0%) versus 9 (4.9%); 13–24 h: 14 (9.7%) versus 7 (3.8%). And the difference was significant ( p = 0.022).…”
Section: Discussionmentioning
confidence: 99%
“…This finding may probably be explained by differences in admission characteristics of the patients 33 34. In fact, severe neurological condition on admission, with reduced consciousness and already permanent brain tissue damage, may lessen the benefits of recanalisation and hamper prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, severe neurological condition on admission, with reduced consciousness and already permanent brain tissue damage, may lessen the benefits of recanalisation and hamper prognosis. It was demonstrated that poor 1-month outcome after BAO can be reliably predicted by older age, absence of hyperlipidaemia, presence of prodromal minor stroke, higher NIHSS score and longer time to treatment 34. Two main criteria that seemed to impact directly on clinical outcomes were (1) baseline ischaemic imaging lesions; and (2) time to recanalisation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation